Basic Principles and Clinical Significance of Oxidative Stress - Joghi Thatha Gowder, Sivakumar (IntechOpen, 2015)
It is a natural phenomenon for all living organisms in the world to undergo different kinds of stress during their life span. Stress has become a common problem for human beings in this materialistic world. In this period, a publication of any material on stress will be helpful for the human society. The book Basic Principles and Clinical Significance of Oxidative Stress targets all aspects of oxidative stress, including principles, mechanisms, and clinical significance. This book covers four sections: Free Radicals and Oxidative Stress, Natural Compounds as Antioxidants, Antioxidants - Health and Disease, and Oxidative Stress and Therapy. Each of these sections is interwoven with the theoretical aspects and experimental techniques of basic and clinical sciences. This book will be a significant source to scientists, physicians, healthcare professionals, and students who are interested in exploring the effect of stress on human life.